Differences in Tumor Immune Microenvironment in Metastatic Sites of Breast Cancer - Lee, Hyunjong; Na, Kwon Joong; Choi, Hongyoon (Frontiers in Oncology, 2021)
Tumor immune microenvironment (TIME) promotes immune escape, allowing for tumor progression and metastasis. In spite of the current evidence of the complicated role of immune cells in promoting or suppressing cancer progression, the heterogeneity of TIME according to the tumor site has been scarcely investigated. Here, we analyzed transcriptomic profiles of metastatic breast cancer to understand how TIME varies according to tumor sites. Two gene expression datasets from metastatic breast cancer of various sites and a single-cell RNA sequencing dataset of primary breast cancer and metastatic lymph nodes were analyzed. The immune cell-type enrichment of each tumor was estimated. Immune cell types were identified by clustering analysis, and the proportions of cell types in TIME were assessed according to the tumor site. Metastatic bone lesions showed more neutrophils than breast lesions. Tumors clustered according to immune cell type were significantly associated with tumor site. In single-cell analyses, the TIMEs of metastatic lymph nodes showed fewer macrophages than those of primary tumors. Differentially expressed gene signatures in the primary tumor and metastatic lymph nodes were associated with macrophage activation. We conclude that metastatic sites show variable enrichment patterns of immune cells, and that the TIME of metastatic lesions should be considered in precise immuno-oncology treatments.